The potential of 3D-FISH and super-resolution structured illumination microscopy for studies of 3D nuclear architecture: 3D structured illumination microscopy of defined chromosomal structures visualized by 3D (immuno)-FISH opens new perspectives for studies of nuclear architecture. - Markaki, Y; Smeets, D; Fiedler, S; Schmid, V; Schermelleh, L; Cremer, T; Cremer, M (2012)
Three-dimensional structured illumination microscopy (3D-SIM) has opened up new possibilities to study nuclear architecture at the ultrastructural level down to the ~100 nm range. We present first results and assess the potential using 3D-SIM in combination with 3D fluorescence in situ hybridization (3D-FISH) for the topographical analysis of defined nuclear targets. Our study also deals with the concern that artifacts produced by FISH may counteract the gain in resolution. We address the topography of DAPI-stained DNA in nuclei before and after 3D-FISH, nuclear pores and the lamina, chromosome territories, chromatin domains, and individual gene loci. We also look at the replication patterns of chromocenters and the topographical relationship of Xist-RNA within the inactive X-territory. These examples demonstrate that an appropriately adapted 3D-FISH/3D-SIM approach preserves key characteristics of the nuclear ultrastructure and that the gain in information obtained by 3D-SIM yields new insights into the functional nuclear organization.